Atypical manifestation of psoriasis in the elderly: possible expression of Mal de Meleda diagnosis review and case report - Onisor, Cristian; Sarpe, Ana-Maria; Niculet, Elena (Frontiers in Medicine, 2025)
Mal de Meleda (MDM) is a rare hereditary skin disorder classified as an autosomal recessive palmoplantar keratoderma, with an estimated prevalence of 1 in 100,000 individuals. It is commonly linked to consanguineous parentage and typically presents during early childhood. The hallmark features of the condition include transient thickening of the palms and soles, skin sclerosis and atrophy, scleroatrophic erythematous lesions, pseudoainhum formation around the digits, and erythema around the mouth. Due to its rarity, many dermatologists may lack clinical familiarity with MDM. Moreover, there is considerable phenotypic similarity between Mal de Meleda and other forms of palmoplantar keratoderma, as well as certain erythrokeratodermas, making clinical differentiation particularly difficult. Therefore, genetic testing to identify causative mutations plays a crucial role in confirming the diagnosis. Genetic alterations in the SLURP1 gene, which encodes the secreted Ly-6/uPAR-related protein 1, have been identified as key contributors to the development of Mal de Meleda (MDM). SLURP1 plays a critical role in maintaining epidermal equilibrium by regulating essential processes such as keratinocyte (KC) proliferation, terminal differentiation, programmed cell death (apoptosis), and cornification. Furthermore, reduced SLURP1 expression has been linked to the pathogenesis of various epithelial cancers, suggesting its broader significance in maintaining epithelial tissue integrity and suppressing tumors. The management of Mal de Meleda remains a clinical challenge, as current therapeutic approaches are largely limited to alleviating symptoms rather than addressing the underlying cause. Systemic retinoids, particularly acitretin, have demonstrated efficacy in reducing epidermal hyperkeratosis and enhancing clinical outcomes. Nonetheless, prolonged administration may lead to significant side effects, necessitating close clinical supervision. This case report contributes to the medical literature by documenting a rare presentation of Mal de Meleda, highlighting the importance of recognizing atypical clinical features and implementing accurate diagnostic and therapeutic interventions. Psoriasis is a chronic, immune-mediated inflammatory dermatosis that exerts a profound effect on patients’ quality of life. The disease typically follows a relapsing-remitting course and is frequently associated with a spectrum of comorbid conditions. In pediatric populations, the etiology of psoriasis is multifactorial, involving a combination of genetic susceptibility, environmental triggers, psychosocial stressors, obesity, physical trauma, cutaneous irritation, and exposure to certain pharmacological agents such as lithium, β-blockers, and tumor necrosis factor (TNF) inhibitors. Moreover, systemic inflammatory disorders like Crohn’s disease and juvenile idiopathic arthritis have been linked to an increased risk of psoriasis in children. The disease burden is considerable in adults, but poses even greater challenges in pediatric patients, where atypical clinical presentations may hinder timely and accurate diagnosis. It is essential for dermatologists to accurately differentiate Mal de Meleda (MDM) from psoriasis, as these conditions may exhibit overlapping clinical features yet diverge significantly in therapeutic response and long-term prognosis. Distinctive diagnostic clues—such as very early disease onset, autosomal recessive mode of inheritance, and the hallmark transgradient pattern of palmoplantar keratoderma—can aid in distinguishing MDM from the more prevalent psoriasis vulgaris. Although biologic therapies targeting TNF-α and IL-17A have shown limited efficacy in MDM, systemic retinoids continue to represent a clinically effective therapeutic option for managing this rare genodermatosis.